2009
DOI: 10.1590/s1984-82502009000400020
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation: effects on blood creatine kinase activity responses to resistance exercise and creatine kinase activity measurement

Abstract: The purpose of this study was to determine the effects of creatine supplementation and exercise on the integrity of muscle fiber, as well as the effect of the supplementation on the creatine kinase (CK) assay measurement. Forty-nine sedentary individuals participated in a double-blind study and were divided into two groups: C (n=26) received 4x5-day packages of 0.6 g.kg -1 of body weight contained 50% of creatine + 50% of dextrose, and P (n=23) received packages containing only dextrose. On the first day the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 23 publications
0
35
0
Order By: Relevance
“…An enzymatic method was used for enzyme activity analysis with commercial kits (BioTe´cnica --Brazil) in Cobas Mira Plus analyzer (Roche, Basel, Switzerland). The same methodology was used in Machado et al (12) and that there was high reproducibility between measurements (intraclass coefficient r = 0.99).…”
Section: Methods Experimental Approach To the Problemmentioning
confidence: 98%
“…An enzymatic method was used for enzyme activity analysis with commercial kits (BioTe´cnica --Brazil) in Cobas Mira Plus analyzer (Roche, Basel, Switzerland). The same methodology was used in Machado et al (12) and that there was high reproducibility between measurements (intraclass coefficient r = 0.99).…”
Section: Methods Experimental Approach To the Problemmentioning
confidence: 98%
“…Several groups have investigated the effects of creatine supplementation on recovery from intense resistance exercise that is more typical of real-world training [115, 139, 140]. Rawson et al [140] examined the effects of creatine supplementation (0.3 g/kg for 5 days; followed by 0.03 g/kg for 5 days) on recovery from a high-intensity squat workout (five sets of 15–20 reps at 50% 1-RM) and found no effect of the creatine on post-exercise strength, serum CK and LDH, ROM, swelling, and DOMS.…”
Section: Creatine Supplementation and Exertional Rhabdomyolysismentioning
confidence: 99%
“…Rawson et al [140] examined the effects of creatine supplementation (0.3 g/kg for 5 days; followed by 0.03 g/kg for 5 days) on recovery from a high-intensity squat workout (five sets of 15–20 reps at 50% 1-RM) and found no effect of the creatine on post-exercise strength, serum CK and LDH, ROM, swelling, and DOMS. Machado et al [139] found no difference in post-exercise CK between creatine- (20 g/day for 5 days) and placebo-supplemented subjects following three sets of ten repetitions of five exercises performed at 75% of 1-RM. Recently, Veggi et al [115] showed that creatine supplementation (20 g/day for 5 days) attenuated the increase in CK and DOMS and decrease in ROM to a greater extent than a placebo following repeated bouts of resistance exercise (four sets of biceps curls at 75% 1-RM).…”
Section: Creatine Supplementation and Exertional Rhabdomyolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have assessed the effects of creatine supplementation on markers of muscle damage following stressful resistance (Cooke et al, 2009;Machado et al, 2009;Rahimi, 2011;Rawson et al, 2007;Rawson et al, 2001;Rosene et al, 2009;Warren et al, 2000) and endurance (Bassit et al, 2008;Bassit et al, 2010;Santos et al, 2004) exercise. Collectively, these studies indicate that creatine either reduces damage and enhances recovery from stressful exercise (Bassit et al, 2008;Bassit et al, 2010;Cooke et al, 2009;Rahimi, 2011;Rosene et al, 2009;Santos et al, 2004) or has no effect (Machado et al, 2009;Rawson et al, 2007;Rawson et al, 2001;Warren et al, 2000). Conflicting results could be related to differences between exercise protocols.…”
mentioning
confidence: 99%